x - 1 /13 + x - 2 / 12 + x - 3 / 15 + 3 = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) x - 2 = -6
x = -6 + 2
x = -4
2) -5 . x - ( -3 ) =13
-5 . x = 13 + ( -3 )
-5 . x = 10
x = 10 : ( -5 )
x = -2
b) -26 - ( x - 7 ) = 0
x - 7 = -26 - 0
x - 7 = -26
x = -26 + 7
x = -19
Bài 2 :
a) 3 - ( 17 - x ) = -12
( 17 - x ) = 3 - ( -12 )
( 17 - x ) = 15
x = 17 - 15
x = 2
1) Do x ∈ Z và 0 < x < 3
⇒ x ∈ {1; 2}
2) Do x ∈ Z và 0 < x ≤ 3
⇒ x ∈ {1; 2; 3}
3) Do x ∈ Z và -1 < x ≤ 4
⇒ x ∈ {0; 1; 2; 3; 4}
14) (x - 2) . (x + 4) = 0
\(\Rightarrow\) x - 2 = 0 hoặc x + 4 = 0
Nếu x - 2 = 0
x = 0 + 2
x = 2
Nếu x + 4 = 0
x = 0 - 4
x = -4
Vậy x \(\in\) {2 ; -4)
15) (x - 2) . (x + 15) = 0
\(\Rightarrow\) x - 2 = 0 hoặc x + 15 = 0
Nếu x - 2 = 0
x = 0 + 2
x = 2
Nếu x + 15 = 0
x = 0 - 15
x = -15
Vậy x \(\in\) {-15 ; 2}
1, 2x - 35 = 15
2x = 15 + 35
2x = 50
x = 50 : 2
x = 25.
2, 3x + 18 = 12
3x = 12 - 18
3x = -6
x = -6 : 3
x = -2.
3, / x - 1 / = 0
=> x \(\in\varnothing\).
4, -13 /x/ = - 26
/x/ = -26 : -13
=> \(\orbr{\begin{cases}x=2\\x=-2\end{cases}}\)
Vậy x \(\in\){ 2 ; -2}.
5,4 - ( 27 - 3 ) = x - ( 13 - 4 )
4 - 24 = x - 9
-20 = x - 9
-x = 9 + 20
-x = 29
x = -29.
6, 47 - ( x + 15 ) = 21
47 - x - 15 = 21
-x - 15 = 21 - 47
-x - 15 = -26
-x = -26 + 15
-x = - 11
x = 11.
7, -5 -( 24 - x) = - 11
-5 - 24 + x = -11
-24 + x = -11 + 5
-24 + x = -6
x = -6 + 24
x = 18.
8, 6 - /x/ = 2
/x/ = 6 - 2
\(\orbr{\begin{cases}x=3\\x=-3\end{cases}}\)
Vậy x \(\in\left\{3;-3\right\}.\)
9, 6 + /x/ = 2
/x/ = 2 - 6
=> x = -4.
2x - 35 = 15
=> 2x = 15 + 35
=> x = 50 : 2
=> x = 25
3x + 18 = 12
=> 3x = 12 - 18
=> x = ( -6 ) : 3
=> x = -2
| x - 1 | = 0
=> x - 1 = 0
=> x = 0 + 1
=> x = 1
-13 * | x | = -26
=> | x | = -26 : ( -13 )
=> | x | = 2
làm ơn giúp tôi với đang cần gấp